ANALYSIS OF THE USE OF E-BANKING AT PT. BANK SYARIAH INDONESIA (BSI) AFTER THE ENACTMENT OF QANUN NO 11 OF 2018 CONCERNING LKS - Fajri, Ikhsan; Zainuri, Hamzah (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
Electronic banking or E-Banking service is the latest innovation presented by Bank Syariah Indonesia (BSI) as a form of commitment to digital technology-based services that aim to facilitate customers in the banking sector. E-Banking services have enabled BSI customers to obtain information, communicate, and conduct banking transactions through electronic media including ATMs, phone banking, electronic fund transfers, internet banking and mobile, This instrument certainly has a very positive impact on users of BSI services in Aceh after the enactment of Qanun No. 11 of 2018 concerning LKS. This study aims to determine how customer perceptions of the ease of use of E Banking and determine customer perceptions of the risks faced in using E-Banking at PT. BSI after the implementation of Qanun No. 11 of 2018 concerning LKS in Aceh. This research method uses a qualitative design with case study research techniques. The types of data collected are primary and secondary data. The results of this study are very useful and can be input for the government and Sharia Financial Institutions to mitigate more quickly related to potential risks that arise both at the internal and external levels of the bank, this is considering that the people of Aceh are currently very sensitive to the form of digital-based services that are often problematic provided by banks to customers.